Plan de mejoramiento para la empresa Sólido Diseño y Arquitectura en la ciudad de Armenia (2014)
Colombia is a country that in the last decade has presented a sustained growth in the construction sector, a real estate boom since the middle of the last decade thanks to new policies the country has grown considerably, which has allowed the market to be related suitable for construction companies and design, therefore the market demands that companies be more competitive and better techniques to address the unmet demand, requiring administrators and managers a competitive and entrepreneurial mindset to be more efficient and profitable . In the department of Quindío there is a company that has decided to change to achieve this continuous improvement, solid company , design and architecture , is an architecture and design firm that has been worked more than five years , achieving a good position and a good growth in recent years , the manager and owner has seen the need to go beyond the administrative empiricism has led at this time, as a result decided to start a plan within the enterprise to excel , through an improvement plan , which begins with an in-depth analysis of how the organization is facing the market (external ) and as found internally. For its development it has been carrying out a plan for improvement in all areas of the company to generate a clear diagnosis and generate appropriate strategies to achieve the goals proposed in this project, in conclusion the decision to implement it took improvement plan for 2014 and make the improvement due to ignoring the recommendations made by the student's degree work and guided under the technical expressed therein.